Hubungan Pengetahuan, Sikap Ibu Hamil dalam Melakukan Antenatal Care (ANC) Selama Pandemi Covid-19 - Dewi Candra Resmi; Romdiyah Romdiyah (Midwifery Care Journal, 2023)
Pregnancy was period that begins with the conception of the egg and sperm cells, which will carry out cell division to become a fetus and will last for 40 to 42 weeks. Antenatal (ANC) visit during the pandemic decreased, approximately 20 pregnant women in a month and by 30 pregnant women in a month during the new normal era. The research aimed to analyzed relationship between knowledge and attitudes of pregnant women and the behavior of carrying out ANC during the COVID-19 pandemic. This research was a quantitative research method used a survey. The total population is 100 pregnant women, and the sample is 45 pregnant women who was been respondents. Data was took used questionnaires in the form of a Google form and in collaboration with regional midwives to distribute it to pregnant women through the Whatshap group. This research was conducted in the Mojotengah health center area. Univariate analysis, described the characteristics of the respondents, bivariate analysis used the chi square test.This study proves that good knowledge of pregnant women and a positive attitude towards pregnant women can motivate pregnant women to carry out ANC routinely during their pregnancy.